2006
DOI: 10.1097/01.aids.0000247579.08449.b6
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of primary antiretroviral drug resistance in antiretroviral-naive HIV-1-infected individuals in a midwest university clinic

Abstract: A total of 192 HIV-1-infected antiretroviral-naive individuals had genotyping performed in our midwest university clinic between 2003 and 2005. The overall prevalence of resistance with either a reverse transcriptase or major protease mutation was 18%. There did not seem to be a significant difference in primary resistance patterns between different modes of HIV transmission (heterosexual versus men who have sex with men), gender or between white and African-American individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
14
0
2

Year Published

2007
2007
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 6 publications
3
14
0
2
Order By: Relevance
“…Similarly, in another U.S. study conducted between 1999 and 2001 among chronically infected patients, the overall estimated prevalence of resistance mutation was 8.8% (14). In a very recent contribution from the United States, an overall prevalence of resistance of 18% among 192 HIV-infected naive patients tested in 2003 and 2004 was reported (6).…”
mentioning
confidence: 90%
“…Similarly, in another U.S. study conducted between 1999 and 2001 among chronically infected patients, the overall estimated prevalence of resistance mutation was 8.8% (14). In a very recent contribution from the United States, an overall prevalence of resistance of 18% among 192 HIV-infected naive patients tested in 2003 and 2004 was reported (6).…”
mentioning
confidence: 90%
“…The activity of antiretroviral drugs (ARVs) can be impeded by the selection and transmission of drug resistance-associated mutations (4,6,11). Yet, few studies of the potential impact of such mutations on viral transmissibility have been carried out (13).…”
mentioning
confidence: 99%
“…Table 4 compares our data with other recent US studies documenting primary resistance in chronically infected patients. Our study had the lowest rate (5%) among these recent studies [1][2][3][4]6,7 in which the rate of resistance ranged from 8% to 18%. The distribution of resistance among the antiretroviral classes was consistent with the recently published data, which showed that NNRTI resistance prevalence was the highest, followed by NRTI and PI resistance.…”
Section: Resultsmentioning
confidence: 56%
“…[1][2][3][4][5]15 Transmitted resistance assumes acquisition from a patient with resistant virus, which was most likely acquired following exposure of the source patient to ART. Thus, a major determinant of the prevalence of ART-associated mutations is access of the population to ART.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation